THE EFFECT OF TALENT MANAGEMENT AND EMPLOYEE COMPENSATION ON THE INCOME OF PDAM TIRTA HANDAYANI - Tina, Sinta Agus; Delasmi Jayanti, Sri (Universitas Terbuka, 2024)
This study aims to analyze the influence of talent management and employee compensation on the revenue of Perusahaan Daerah Air Minum (PDAM) Tirta Handayani Gunung Kidul, Bribin Branch. The research employs a quantitative descriptive approach where the data is numerical. The study was conducted at PDAM Tirta Handayani Gunungkidul, Bribin Branch, surveying 36 respondents during the survey period from February to April 2024. The sampling technique used in this study is the probability sampling method. The data analysis method utilized is multiple linear regression analysis. Based on the analysis results, it was found that talent management has a significant impact on the company's revenue. It was discovered that talent development strategies, recruitment, and employee retention positively contribute to increasing the company's revenue. Additionally, employee compensation also has a significant impact on the company's revenue. Employees who feel that they are being compensated fairly and in accordance with their contributions tend to be more motivated to improve their performance, which in turn will positively affect the company's revenue. In this context, the management of PDAM Tirta Handayani Gunung Kidul, Bribin Branch, is advised to pay more attention to talent management and the employee compensation system. Investing in talent development and providing fair compensation can be an effective strategy to improve employee performance and overall company revenue.